RECOGNITION OF FACIAL EXPESSION USING FACIAL MOVEMENT FEATURES (International Journal of Engineering and Computer Science, 2014)
This paper work presents an approach to solve recognition of facial expression  using ‘salient’ distance features, which are obtained by extracting patch-based 2D Gabor features, selecting the ‘salient’ patches, and performing patch matching operation The experimental results demonstrate high correct recognition rate (CRR), significant performance   improvements due to the consideration of facial +element and muscle movements, promising results under face registration errors, and fast processing time. The comparison with the state-of-the-art performance confirms that the proposed approach achieves the highest CRR on the JAFFE database and is among the top performers on the Cohn-Kanade (CK) database.